Mechanical and numerical behavior of groups of screw (type) piles founded in a tropical soil of the Midwestern Brazil. (June 2015) - Mendoza, C.C.; Cunha, R.; Lizcano, A.
Abstract: This paper presents and discusses the behavior of standard groups and piled rafts constructed with helical screw piles founded in the typical soil of the Federal District of Brazil (DF). The paper initially characterizes the soil deposit of a new Experimental Site in the DF via laboratory (standard characterization, triaxial) and field (standard penetration and flat dilatometer) tests. It then moves to explain a recently adjusted (hypoplasticity) constitutive model that takes on consideration the inherent soils structure to simulate the behavior of this typical geotechnical material. The model was calibrated via point load test analyses and incorporated into a finite element methodology (FEM) routine internal to the traditional Abaqus software. Real scale field load tests on standard pile groups and piled rafts executed with this pile type were carried out in the new site. FEM analyses were used to calibrate the model and to expand the knowledge on the shearing mechanisms, generated stresses, displacement fields, load sharing, group efficiency, and on the contribution of the supporting raft to the overall systems performance. Conclusions of practical and academic interest are given for this new type of foundation employed in the region.